2018
DOI: 10.1002/jocb.364
|View full text |Cite
|
Sign up to set email alerts
|

Positive Affect Mediates the Relationship Between Self‐efficacy and Innovative Behavior in Entrepreneurs

Abstract: Innovativeness is one of the crucial factors allowing companies to grow, and innovative behavior of entrepreneurs is an important source of firm innovativeness and business success. This study aims to better understand self‐regulatory mechanisms stimulating the innovative behavior of entrepreneurs. We have tested the mediation model in which work‐related affect (enthusiasm, comfort, anxiety, and depression) mediates the relationship between work self‐efficacy and innovative behavior. A longitudinal study with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 84 publications
6
45
1
4
Order By: Relevance
“…The SDT literature has reported a positive association between intrinsic motivation and performance and behavioral outcomes [34,38,42,43,44]. Consistent with these findings, we propose that intrinsic motivation has a positive relationship with job performance.…”
Section: Theoretical Background and Hypothesis Developmentsupporting
confidence: 85%
“…The SDT literature has reported a positive association between intrinsic motivation and performance and behavioral outcomes [34,38,42,43,44]. Consistent with these findings, we propose that intrinsic motivation has a positive relationship with job performance.…”
Section: Theoretical Background and Hypothesis Developmentsupporting
confidence: 85%
“…We also did not investigate mechanisms responsible for the innovative behaviour of entrepreneur-firm owners, which may be different than those of employees [92]. This investigation awaits future studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, both leaders and employees being humorous (Quadrant 2) means that both employees and leaders have a positive emotional experience. Positive emotions expand the scope of cognition and attention (Fredrickson, 2013), which is conducive to the generation and implementation of innovative ideas (Mielniczuk and Laguna, 2020). In addition, the intrinsic motivation brought by humor (Weinstein et al, 2013;Chang et al, 2015) is the internal driving force of innovation (Su et al, 2020).…”
Section: H1mentioning
confidence: 99%
“…Previous research has found that employees with intrinsic interest in innovation voluntarily engage in innovative behavior, because they naturally prefer and enjoy the engagement in innovative activities ( Shin et al, 2017 ). In addition, humorous employees are also good at using positive emotions to expand thinking flexibility ( Baas et al, 2008 ), and these employees experiencing positive affect are more likely to generate new ideas and stimulate innovative behavior ( Mielniczuk and Laguna, 2020 ). Thus, when employee humor is higher than his or her leader, it means that the employee has stronger intrinsic motivation and more emotional resources for innovative behavior.…”
Section: Theories and Hypothesesmentioning
confidence: 99%